2010
DOI: 10.1177/1049732310367502
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Messaging for Younger Women: Gender, Femininity, and Risk

Abstract: Evidence linking both active smoking and secondhand smoke exposure to premenopausal breast cancer makes the development of health messages specific to younger women a pressing priority. To determine how to communicate information about this modifiable breast cancer risk to young women, we analyzed a selection of 32 recent English-language breast cancer messages and campaigns that targeted young women. In addition, we obtained young women's responses to three breast cancer campaign images during focus group dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 32 publications
(38 reference statements)
0
24
0
1
Order By: Relevance
“…Such perceptions seem similar among women worldwide. Studies from different women populations in Asia, Africa, Europe and America also reported that women are very concerned with their breasts, as they believe breasts shape up their identity [41-45]. Perhaps those who work in primary health care services might use this as reinforcing factor to encourage women to see their doctors when they feel something is wrong with their breasts.…”
Section: Discussionmentioning
confidence: 99%
“…Such perceptions seem similar among women worldwide. Studies from different women populations in Asia, Africa, Europe and America also reported that women are very concerned with their breasts, as they believe breasts shape up their identity [41-45]. Perhaps those who work in primary health care services might use this as reinforcing factor to encourage women to see their doctors when they feel something is wrong with their breasts.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have suggested strategies similar to those grouped within our ‘target and tailor’ approach to health education to improve the uptake of cancer screening services. Many note that information needs may be unique depending on age (Haines et al. 2010), culture (Johnson et al.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have suggested strategies similar to those grouped within our 'target and tailor' approach to health education to improve the uptake of cancer screening services. Many note that information needs may be unique depending on age (Haines et al 2010), culture (Johnson et al 1999, Bottorff et al 2001) and health practices (Hilton et al 2001). It is frequently acknowledged that messaging must be carefully formulated to align with communicative patterns of the target group (Friedman & Hoffman-Goetz 2006, Hoffman-Goetz & Friedman 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Findings of a breast cancer message and campaign analysis revealed imagery that "sexually objectifies young women's breasts and bodies" (Haines et al 2010): evidence of what Connell (1987) called "emphasized femininity" (183) designed to socialize women into serving as sex objects. Sweeney (2012) qualified breast cancer as a site for collective action since the 1990s, "one of the most popular and influential health social movements of the last 25 years" (76) which encourages women to express (rather than suppress) their feelings of sorrow, grief, and aggression.…”
Section: Breast Cancer and Collective Actionmentioning
confidence: 98%